Archaeal contribution to carbon-functional composition and abundance in China’s coastal wetlands: Not to be underestimated - Yang, Meiling; Liu, Na; Wang, Baoli; Li, Yajun; Li, Jianfeng; Liu, Cong-Qiang (Frontiers in Microbiology, 2022)
Microbial diversity, together with carbon function, plays a key role in driving the wetland carbon cycle; however, the composition, driving factors of carbon-functional genes and the relationship with microbial community have not been well characterized in coastal wetlands. To understand these concerns, microbes, carbon-functional genes, and related environmental factors were investigated in twenty wetlands along China’s coast. The results indicate that carbon-functional gene composition is dominated by archaeal rather than bacterial community and that Nanoarchaeaeota is the dominant archaeal phylum associated with carbon cycling in anoxic sediments. Compared with microbes, carbon-functional composition was more stable because they showed the highest Shannon diversity and archaeal functional redundancy. Deterministic processes dominated microbial community, and stochastic processes were more important for carbon-functional genes. Labile Fe governed archaeal and carbon-functional composition by coupling with nitrogen and carbon biogeochemical cycles, while bacterial community was affected by NH4-N and SOC/SON. This study highlights the predominant contributions of archaea to carbon-functional genes and to the stability of carbon-functional composition, thus providing new insights into the microbial dominance of the carbon cycle and the evaluation of carbon function in coastal wetlands.